Retention in primary care among unstably housed residents of a low-income, inner-city neighborhood with a high prevalence of substance use and related disorders - M. Gumprich; W. Zhang; J. Li; K. Salters; R. Barrios; P. Sereda; C. Stanley; R. Joe; D. Hall; V. Lima; G. Sincraian; A. Marante Changir; et al. (BMC, 2024)
Abstract Introduction Access to and engagement with primary healthcare can be difficult for marginalized low-income populations residing in inner cities in high-income countries. We designed a study to examine retention in primary care among clients of a novel interdisciplinary primary care clinic in the Downtown Eastside of Vancouver, Canada who did not previously have access to care. Methods Beginning in June 2021, clients of the Hope to Health clinic were offered enrolment in a cohort study which involved a baseline and follow-up surveys every six months, and linking their data to information from the clinic's electronic medical records. We used Chi-square or Fisher's Exact test and Wilcoxon rank sum test to compare clients who were lost to follow-up (LTFU) or deceased, with clients who were retained in care at the end of follow-up, Cox proportional hazards modeling was used to examine independent associations with mortality or LTFU. Results Among 425 participants enrolled, the median age was 50 years (IQR 40-59), 286 (67.3%) participants were men and 128 (25.4%) were unstably housed at enrollment. Among 338 participants with at least six months of follow-up after enrolment, 262 participants (67.5%) were retained in care, 20 (5.2%) had moved, 57 (14.7%) were classified as LTFU, and 28 (7.2%) had died with a median of 19.9 months of follow-up time. The risk of death or LTFU was independently associated diagnosed with alcohol use disorder (AUD) (adjusted hazard ratio [AHR] = 2.23 vs. not; 1.38-3.60), frequency of medical doctor visits (AHR = 0.69 per visit per 3 months; 0.60-0.79) and social work visits (AHR = 0.73 per visit per 3 months; 0.59-0.90. Stimulant use disorder or asthma were not significantly associated with retention in care. Conclusion We found that a primary healthcare model of care was successful in retaining over two-thirds of clients in primary healthcare after more than 18 months of follow-up. Additional supports for those diagnosed with alcohol use disorder are needed to retain them in care.